Analysis of Transverse Flow Characteristics in LBE-cooled Wire-wrapped Fuel Assembly - CONG Tenglong;WANG Junjie;XIAO Yao;LIU Maolong;GU Hanyang (Yuanzineng kexue jishu, 2022)
LBE-cooled fast reactor (LBFR) has a promising application prospect in energy generation and transmutation of highlevel radioactive waste. Wirewrapped fuel rods are usually used in LBFR to reach high heat transfer efficiency and selfsupport. The wire spacer has a great influence on the transverse flow and interchannel mixing, and leads to a nonuniform temperature profile over the fuel rod surface. Therefore, accurate prediction of the transverse flow mixing characteristics in the wirewrapped bundle channel is the basis of thermalhydraulic safety analysis of LBFR. In the present study, a CFD modeling and simulation for a LBEcooled 7pin wirewrapped fuel assembly was carried out based on RANS method. The simulation results were firstly compared with the experimental data from the literature. A good agreement demonstrated the capability of the employed approach to predict the flow field in the rod bundle. Then, the threedimensional transverse flow mixing behaviors of LBE in single wirewrapped fuel and multi wire-wrapped fuel assemblies were analyzed in detail. The results show that the maximum transverse flow velocity in the central sub-channel of the single wirewrapped fuel assembly does not exceed 19% of the axial flow velocity. The transverse flow direction and secondary flow center change periodically with height. In the single wirewrapped fuel assembly, the transverse flow at the interface of the central subchannel is distributed as a trigonometric function along the axis. When the wire spacer coincides with the interface of the central subchannel，the transverse flow and the transverse flow mixing index tend to zero. When the wire spacer is perpendicular to the interface, the transverse flow and the transverse flow mixing index reach the peak. The transverse flow mixing index is not sensitive to Reynolds number in the turbulent zone, but is strongly correlated to the structural parameters of the assembly, which means that the lateral mixing in the wirewrapped bundle is dominated by the flow sweeping mechanism, rather than turbulent mixing. Compared with the single wire-wrapped fuel assembly, the transverse flow distribution of the multi wirewrapped fuel assembly is more uniform and more secondary flow vortex can be observed. The swirling directions of the LBE around the two adjacent fuel rods in the multi wirewrapped fuel assembly are opposite. That is, there are two opposite transverse flow directions on the interface of the central subchannel in the multi wirewrapped fuel assembly.